Efeitos da experiência de viagem em turistas idosos: uma análise quanto às relações entre turismo e qualidade de vida - Bruno Lima Machado (2018)
The present research aimed to understand the effects of travel experience on elderly tourists through the relationship between tourism and quality of life. And to achieve this goal, the research was divided into two studies that relate to each other. Study 1 refers to a systematic review, in national databases, of identifying and raising characteristics of research on tourism and quality of life in Brazil. The second study is an analysis of the relationships that may exist between sociodemographic profile, characteristics of the trip, evaluation of the effects of the trip and evaluation of the quality of life of the elderly tourists surveyed. As a method for the first study, three distinct moments were used: first, the definition of the criteria for inclusion and exclusion of searches, databases, dates and keywords; during, which concerns the search itself; and then, referring to the description and careful analysis of the selected researches. The main findings of the systematic review confirm the existence of few and limited research that relates tourism and quality of life in the national databases. Thirty-two surveys were selected, but only seven of them used elderly tourists as a population heard. At the end of the systematic review, it is concluded that tourism contributes positively to the quality of life of elderly tourists. As for the method of study 2, it was a survey type survey, with a predominantly quantitative approach. A total of 98 elderly tourists (60 and older) participated in virtual groups of Facebook, from October 2017 to January 2018, who traveled in the last 12 months. For the research instrument, five questionnaires were used: sociodemographic, characteristics of the trip, satisfaction of the effects of the trip, evaluation of the elderly-specific quality of life (WHOQOL-OLD) and general quality of life evaluation (WHOQOL-Bref). For the data analysis, quantitative tests were applied, such as frequency, mean, standard deviation, Pearson correlation test and non-parametric Mann-Whitney test; and for the analysis of the qualitative part the content analysis was applied. The main findings of study 2 confirm that tourism actually contributed to the quality of life of the elderly in this research in a direct and significant way. That is, the elderly tourists indicated that, taking into account their sociodemographic profile and the characteristics of the trip, there is a positive satisfaction about the effects of the trip in their quality of life and there is a positive perception both in the specific quality of life of the elderly, and quality of life. Aspects such as religion, family income, destination visited, duration of travel and cost of travel are factors that can infer differently in the quality of life of the elderly. Already aspects such as gender, age, marital status and exercise of paid activity do not interfere in a different way in the elderly tourists of this research.